Validation and Reliability Study of the Neurotic Leadership Perception Scale - Yalçın, Aslı Yıldız; Özdemir, Tuncay Yavuz; Demir, Yasin (Kahramanmaras Sutcu Imam University, 2025)
The aim of this study was to develop the Neurotic Leadership Perception Scale and to test its validity and reliability. A total of 848 teachers working in a province in the eastern part of Türkiye during the 2022-2023 academic year participated in the study. Exploratory factor analysis, confirmatory factor analysis, Cronbach's Alpha values for criterion validity and reliability were used to analyze the validity and reliability of the data. Exploratory factor analysis showed that two factors explained 65% of the total variance. Confirmatory Factor Analysis demonstrated acceptable goodness of fit for the two-factor model with CFI (0.95) and for the 24-item scale with RMSEA (0.06). Pearson Product-Moment Correlation Analysis was used to test the criterion validity of the scale, and the findings indicated a moderately positive significant relationship between neurotic leadership perception and burnout, as well as a moderately negative relationship with empowering leadership. The Cronbach's Alpha coefficient was found to be 0.95 for Factor 1, 0.95 for Factor 2, and 0.97 for the overall scale, indicating a high level of reliability. The analyses and findings suggest that the Neurotic Leadership Perception Scale exhibited a valid and reliable structure at a general level.

Bu çalışmanın amacı, Nevrotik Liderlik Algısı Ölçeği'ni geliştirmek ve geçerlik ve güvenirliğini test etmektir. Çalışmaya 2022-2023 eğitim-öğretim yılında Türkiye'nin doğusundaki bir ilde görev yapan toplam 848 öğretmen katılmıştır. Verilerin geçerlik ve güvenirliğini analiz etmek için açımlayıcı faktör analizi, doğrulayıcı faktör analizi, ölçüt geçerliliği ve güvenirliği için Cronbach's Alpha değerleri kullanılmıştır. Açımlayıcı faktör analizi, iki faktörün toplam varyansın %65'ini açıkladığını göstermiştir. Doğrulayıcı Faktör Analizi, iki faktörlü model için CFI (0,95) ve 24 maddelik ölçek için RMSEA (0,06) ile kabul edilebilir uyum iyiliği göstermiştir. Ölçeğin ölçüt geçerliliğini test etmek için Pearson Ürün-Anlık Korelasyon Analizi kullanılmış ve bulgular nevrotik liderlik algısı ile tükenmişlik arasında orta derecede pozitif anlamlı bir ilişki, güçlendirici liderlik ile ise orta derecede negatif anlamlı bir ilişki olduğunu göstermiştir. Cronbach's Alpha katsayısı Faktör 1 için 0,95, Faktör 2 için 0,95 ve genel ölçek için 0,97 olarak bulunmuş olup, bu yüksek düzeyde bir güvenirliliğe işaret etmektedir. Analizler ve bulgular, Nevrotik Liderlik Algısı Ölçeği'nin genel düzeyde geçerli ve güvenilir bir yapı sergilediğini göstermektedir.
Nevrotik Liderlik Algısı Ölçeğinin Geçerlilik ve Güvenilirlik Çalışması
Keywords: Management Psychology; Yönetim Psikolojisi